Re-distribution of brachytherapy dose using a differential dose prescription adapted to risk of local failure in low-risk prostate cancer patients. Issue 3 (June 2015) - Rylander, Susanne; Polders, Daniel; Steggerda, Marcel J.; Moonen, Luc M.; Tanderup, Kari; Van der Heide, Uulke A.
Abstract Background and purpose We investigated the application of a differential target- and dose prescription concept for low-dose-rate prostate brachytherapy (LDR-BT), involving a re-distribution of dose according to risk of local failure and treatment-related morbidity. Material and methods Our study included 15 patients. Multi-parametric MRI was acquired prior to LDR-BT for gross tumor volume (GTV) delineation. Trans-rectal ultrasound (US) images were acquired during LDR-BT for prostate gland- (CTVProstate) and organs at risk delineation. The GTV contour was transferred to US images after US/MRI registration. An intermediate-risk target volume (CTVProstate) and a high-risk target volume (CTVHR = GTV + 5 mm margin) were defined. Two virtual dose plans were made: Planrisk-adapt consisted of a de-escalated dose of minimum 125 Gy to the CTVProstate and an escalated dose to 145–250 Gy to the CTVHR; Planref included the standard clinical dose of minimum 145 Gy to the CTVProstate. Dose-volume-histogram (DVH) parameters were expressed in equivalent 2 Gy fractionation doses. Results The median D90% to the GTV and CTVHR significantly increased by 44 Gy and 17 Gy, respectively when comparing Planrisk-adapt to Planref. The median D10% and D30% to the urethra significantly decreased by 9 Gy and 11 Gy, respectively and for bladder neck by 18 Gy and 15 Gy, respectively. The median rectal D2.0 cm3 had a significant decrease of 4 Gy, while the median rectal D0.1 cm3 showed an increase of 1 Gy. Conclusions Our risk adaptive target- and dose prescription concept of prescribing a lower dose to the whole gland and an escalated dose to the GTV using LDR-BT seed planning was technically feasible and resulted in a significant dose-reduction to urethra and bladder neck.